(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1999)
Three sphinctozan sponges: Amblysiphonella sp., Colospongia sp. and the new species Deningeria iannacei n. sp., are described from a loose boulder derived from Triassic dolomites ("Dolomia principale") of the Argentino valley in Northern Calabria (Southern Italy). All three genera are reported for the first time from Calabria. The sphinctozoans are associated with other sponges (inozoans, "sphinctozoans," "hydrozoans", chaetetids), "microproblematica", foraminifers, abundant worm tubes, biogenic crusts, and rare dasycladacean algae. The age of the association is referred to Upper Triassic (Norian-Rhaetian) on the basis of its similarity to the classic reef assemblages of Upper Triassic in the Tethys realm and by the close proximity of the boulder to the well dated (macrofauna) outcropping Upper Triassic carbonate successions.